The History of Habits: A Critical Unknown in the History of Chinese Medicine - Shigehisa Kuriyama (Wolters Kluwer Health/LWW, 2023)
This essay articulates a new conceptual distinction - that between repertories and habits - and urges that the history of habits is the most critical unknown in the study of Chinese medical history.